Acidente de trabalho: precarização da força de trabalho nos frigoríficos da região oeste do Paraná - Leite, Nilton Batista (2015)
This research aims understand the deflection of the State reform in the working-welfare laws and their impacts on the food industry workers health, specifically the cold rooms. Our bibliographic investigation and analytical work about the State counter-reform is guided since the Collor de Mello government until the Dilma Roussef government, exposing the changes, and in some moments suppressions, that the social legislation, with an highlight, to the welfare and worker, has suffered in face of neoliberal thrusts in the country, mainly from what was conventionalized as the Washington Agreement . These impacts over the workers in general, and specifically, by the workers of the cold rooms production chain, which lack of protection is evidenced in the working accidents. It is exposed in another moment the duality between the importance of the agribusiness to the economical growth, in detriment of an emancipatory work. In this context of precarious work, working accidents are shown as refractions of the social question . In the agribusiness case, specifically in the cold room conglomerate, the working conditions are deplorable, together with the lack of an effective inspection by the entities that protect the workers, propitiate the subsistence of an unhealthy environment, prone in the generation of several working accidents. And in this setting, at FRIG , a real cold chamber located on the west region of Paraná and on the micro-region of Toledo, that the research is materialized by means of the analysis of the Working Accidents Communications, starting from January 2008 to June 2014, making explicit the extreme worker exploitation in this specific manufacturing environment and the killing of his dreams.